Prognostic role of global work efficiency in patients undergoing transcatheter aortic valve implantation. (3rd October 2022) - Ilardi, F; Manzo, R; Franzone, A; Angellotti, D; Avvedimento, M; Iapicca, C; Manzi, L; Verde, N; Simonetti, F; Castiello, D; Leone, A; Mariani, A; et al.
Abstract: Background: Non-invasive myocardial work (MW) quantification has emerged in the last years as an alternative echocardiographic tool for myocardial function assessment. Its role in patients with severe aortic stenosis (AS) after aortic valve implantation (TAVI) has not been adequately investigated. Purpose: We aimed to evaluate MW indices as early echocardiographic markers of LV reverse remodeling within a month after TAVI and their prognostic value. Methods and results: We conducted a single-centre prospective study, enrolling 88 consecutive patients (mean age 79.9±6.4 years, 35% males) with AS undergoing TAVI between April 2018 and 2021, selected from the EffecTAVI registry. Exclusion criteria were prior valve surgery, atrial fibrillation, left bundle branch block (LBBB) at baseline and and suboptimal quality of imaging. Echocardiographic assessment was performed before TAVI and at 30-day follow-up, including quantification of 2D global longitudinal strain (GLS), global work index (GWI), global constructive work (GCW), global wasted work (GWW) and global work efficiency (GWE). LV peak systolic pressure was estimated non-invasively from the sum of systolic blood pressure and trans-aortic mean gradient. One month after the procedure, there was a significant improvement of LV GLS (−18.4±4.2 vs −19.5±4.2%, before and after TAVI respectively, p=0.006), a significant reduction of GWI (2406±567 vs 1908±479 mmHg%, p<0.001), GCW (2783±616 vs 2202±463 mmHg%, p<0.001), and GWW (238±203 vs 173±127 mmHg%, p=0.002). Conversely, MWE did not change early after intervention (90.4±6.2 vs 91.4±5.1%, p=0.113). After TAVI, 32 patients (36.4%) developed LV dyssynchrony due to LBBB or pacemaker implantation. When the population was divided according to the presence or absence of LV dyssynchrony at 30-day follow-up, a significant reduction in GWW was found only in the those without dyssynchrony (241±229 vs 142±103 mmHg% before and after TAVI, p<0.001). Consistently, in this subgroup, MWE significantly improved after TAVI (90±7 vs 93±5%, p=0.001), while a trend of MWE reduction was observed in patients who developed dyssynchrony after TAVI (91±5 vs 89±5%, p=0.110). In the overall population, a 30-day value of MWE≤92% was associated with an increased rate of cardiovascular events (composite of all-cause death and rehospitalization for heart failure) at 1-year follow-up (29.5% vs 4.8%, long rank p=0.003). In multivariable Cox-regression analysis, adjusted for confounders, GWE after TAVI (HR: 0.892, CI: 0.817–0.974; p=0.011) was independently associated with events at 1-year follow-up. Conclusions: In patients with severe AS undergoing TAVI a significant reduction of GWW and improvement of MWE can be detected only in those who do not develop LV dyssynchrony. In this setting, MWE≤92% early after TAVI is associated with poor outcome. Thus, MWE could represent an alternative tool for myocardial function assessment and prognostic evaluation in patients receiving TAVI. Funding Acknowledgement: Type of funding sources: None.